The development of the political party system in the Ciskei - Ka Tywakadi, Gordon Renton (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 1978)
(p. 1) The Ciskei homeland, which is a 'sub-state' of the Republic of South Africa, attained a semi-autonomous status as a result of the implementation of the Bantustan policy of the Government of the Republic of South Africa. This semi-autonomous status introduced a Westminster type of parliamentary system which in turn brought into being a political party system. The purpose of this thesis is to investigate, amongst other things, the roles played by these political parties:- i) What role would the political parties play in the struggle of the Ciskeians for equal political rights vis - a-vis white South Africa? ii) Whose interests would those political parties serve? iii) This semi-autonomous status has resulted in the juxtaposing of traditional and modern political institutions. The political institutions that have emerged, include inter alia, legislative assemblies and political parties. These modern political institutions have been superimposed on traditional political institutions. What effect(s) would the one have on the other? iv) Would the development of political parties lead to the establishment of a one, two or dominant party system? In order that the above questions may be answered, i) An attempt will be made to define a political system, illustrating the concept with examples taken from the Republic of South Africa political scene and at the same time, attention will be directed to the relationship between the Republic of South Africa and the Ciskei. ii) When investigating the political party and the political party system, the role played by the political parties and the political party system in the relationship between the Republic of South Africa and the Ciskei will be defined.,Ciskei (South Africa) -- Politics and government,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Political parties -- South Africa -- Ciskei; Elections -- South Africa -- Ciskei